Role of locking compression plate in management of metaphyseal fractures in osteoporotic bones: an experimental study from rural Maharashtra - Rathi, Prasanna; Paknikar, Kiran P.; Malve, Shekhar P.; Kulkarni, Govind S.; Kulkarni, Milind G.; Kulkarni, Sunil G.; Takalkar, Anant A. (International Journal of Research in Orthopaedics, 2019)
Background: Osteoporosis is multi factorial disease, which is caused by complex interaction between genetic and environmental factors that influence bone turnover, bone mass, skeletal geometry and risk factors. Distal femur fracture needs aggressive management in terms of open reduction and internal fixation with locking compression plate and early mobilization. Objectives were to study the role of locking compression plate in the management of osteoporotic metaphyseal fractures. Methods: Present study is a prospective study comprising of 50 patients who sustained various fractures in different bones of body due to osteoporosis and were treated using locking compression plate (LCP). All patients were evaluated for effectiveness of LCP. Results: In present series majority of patients (44%) fall in age group of 61-70 years having senile osteoporosis, followed by 12 (24%) from 51-60 years age group. Majority of the cases involved were distal femur fractures (50%). 15 i.e. 30% cases were fracture of proximal tibia and 20% were fracture of proximal humerus. 96% had osteoporosis. C1 type of fracture was commonly seen in 6 (12%) patients. The mean constant score at one month was 58 and at the end of one year it was 80. The mean oxford score at one month was 28 and at the end of one year it was 38. Conclusions: Locking compression plate is an ideal implant for fixation in metaphyseal osteoporotic bones when used methodically.